Public Profit Sharing - Ronnie Schöb (Center for Economic Studies and ifo Institute (CESifo), 2001)
Many countries suffer from persistently high unemployment rates. The scope for labour market reforms is often limited to measures that hurt neither shareholders nor workers. This paper develops a policy proposal, which allows the government to reduce wage costs without changing the income positions as determined in the process of wage negotiations. It is shown that the introduction of public profit sharing, i.e. substituting profit share for social security contributions, can boost employment both in the short run and the long run. Calibrating the model and comparing the results with recent empirical findings about the impact of labour taxation confirm the theoretical findings.
Keywords: 330; Public profit sharing; trade unions; unemployment; labour market reform